Combined administration of recombinant human megakaryocyte growth and development factor and granulocyte colony-stimulating factor enhances multilineage hematopoietic reconstitution in nonhuman primates after radiation-induced marrow aplasia. - A M Farese; P Hunt; L B Grab; T J MacVittie (The Journal of Clinical Investigation, 1996)
This study compared the therapeutic potential of recombinant, native versus pegylated megakaryocyte growth and development factor (rMGDF and PEG-rMGDF, respectively), as well as that of the combined administration of PEG-rMGDF and r-methionyl human granulocyte colony-stimulating factor (r-metHuG-CSF) on hematopoietic reconstitution after 700 cGy, 60Co gamma, total body irradiation in nonhuman primates. After total body irradiation, animals received either rMGDF, PEG-rMGDF, r-metHuG-CSF, PEG-rMGDF and r-metHuG-CSF or HSA. Cytokines in all MGDF protocols were administered for 21-23 d. Either rMGDF, PEG-rMGDF, or PEG-rMGDF and r-metHuG-CSF administration significantly diminished the thrombocytopenic duration (platelet count (PLT) < 20,000 per microliter)to o.25, 0, 0.5 d, respectively, and the severity of the PLT nadir (28,000, 43,000, and 30,000 per microliter, respectively) as compared with the controls (12.2 d duration, nadir 4,000 per microliter), and elicited an earlier PLT recovery. Neutrophil regeneration was augmented in all cytokine protocols and combined PEG-rMGDF and r-metHuG-CSF further decreased the duration of neutropenia compared with r-metHuG-CSF alone.These data demonstrated that the administration of PEG-rMGDF significantly induced bone marrow regeneration versus rMGDF, and when combined with r-metHuG-CSF significantly enhanced multilineage hematopoietic recovery with no evidence of lineage competition.